Iron Acquisition Mechanisms and Their Role in the Virulence of Acinetobacter baumannii - Cook-Libin, Shoshana; Sykes, Ellen M E; Kornelsen, Vanessa; Kumar, Ayush (Infection and immunity, 2022)
Iron is an essential element for survival of most organisms. One mechanism of host defense is to tightly chelate iron to several proteins to limit its extracellular availability. This has forced pathogens such as Acinetobacter baumannii to adapt mechanisms for the acquisition and utilization of iron even in iron-limiting conditions. A. baumannii uses a variety of iron acquisition strategies to meet its iron requirements. It can lyse erythrocytes to harvest the heme molecules, use iron-chelating siderophores, and use outer membrane vesicles to acquire iron. Iron acquisition pathways, in general, have been seen to affect many other virulence factors such as cell adherence, cell motility, and biofilm formation. The knowledge gained from research on iron acquisition led to the synthesis of the antibiotic cefiderocol, which uses iron uptake pathways for entry into the cell with some success as a novel cephalosporin. Understanding the mechanisms of iron acquisition of A. baumannii allows for insight into clinical infections and offer potential targets for novel antibiotics or potentiators of current drugs.